Exploring Learner Autonomy in Language Classrooms: A Quasi-Experimental Approach (Al-Qamar, 2025)
Learner autonomy is a western concept that came in language education via main stream psychology and theories of education. The main aim of this research is to measure the impact of learner autonomy on language proficiency of BS English learners of Southern Punjab. The researcher followed the quasi-experimental research design following pre-test and posttest methodology. To conduct this test the researcher devised a Language Proficiency Test that includes all the four language skills i.e. reading, writing. Listening and speaking. Two classes of BS English 8th semester were selected as control group and experimental group. The students belonging to control group were taught a module in traditional teacher-controlled method while the experimental group was taught following Nunan’s five stages model of learner autonomy. Language proficiency Test was conducted for both the classes as pre-test and the same test was conducted after the completion of one semester. Results obtained in this way indicate that the principles of learner autonomy, if followed properly, can enhance language proficiency of our learners. Learner autonomy and teacher autonomy should be incorporated in teacher training programs.
Keywords: Learner Autonomy; Quasi Experimental model; Language classroom